Theaters of Sound: : listening, immersion, strangeness - Martins, Jose Batista Dal Farra (Revista Brasileira de Estudos da Presença, 2024)
In the Theaters of sound, sound stages: sonority and visuality are in solidarity. The article develops in this field, in a theoretical and poetic mode, according to an axis that problematizes the concepts of immersion and strangeness, articulated with presence and absence. The essay is driven by conceptual prospecting, considerations on the anatomical incision of sound, on the relations between scene and technology, and a series of listening gestures, in dialogue with theatrical poetics, such as: Elettra, by Hugo von Hofmannsthal, with sound by Hubert Westkemper (2004); Ouverture Alcina, by Nevio Spadoni, with Ermanna Montanari and music by Luigi Ceccarelli (2009); Not I / Eu Não, by Samuel Beckett, with Maria Alice Vergueiro (1986) and Eislermaterial, directed by Heiner Goebbels (1998).